Philippines : Technical Assistance Report on Road Map for a Pro-Growth and Equitable Tax System. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
The Technical Assistance Report on the Philippines' road map for a pro-growth and equitable tax system is examined. Tax revenue has declined over the last decade in the Philippines owing to generous and expanding tax incentives, tariff rate reduction, deteriorating tax compliance caused by ineffective and inefficient revenue administration, and a gradual erosion of excise revenue owing to nonindexation. One of the key reasons for providing tax incentives in the Philippines is concern that the country needs to be competitive with other countries in the region to attract foreign direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet